Analysis of The Effectiveness and Contribution of Entertainment Tax Revenue to Regional Revenue - Fadyah, Diva Mahirah; Barus, Elida Elfi (DAS Institute, 2025)
Entertainment tax is a significant source of Local Own Revenue (PAD), yet its effectiveness in enhancing PAD varies across different regions. This study aims to analyze the factors influencing entertainment tax revenue and taxpayer compliance, as well as to evaluate the role of tax administration in improving the effectiveness of tax collection. The methodology employed is a literature review, involving an in-depth analysis of theories and previous research findings related to entertainment taxation, taxpayer compliance, and tax administration. The results indicate that taxpayer awareness, transparent tax policies, and efficient tax administration are crucial for optimizing entertainment tax revenue. However, challenges such as low taxpayer compliance and inconsistent policies across regions hinder its potential. The study recommends enhancing taxpayer education and outreach, improving tax administration through digitalization and stricter oversight, and harmonizing tax policies across regions. By implementing these recommendations, it is expected that entertainment tax can contribute more significantly to PAD and support sustainable regional development.